Titans. Vol. 2, The dark-winged queen - Taylor, Tom, 1978- (DC Comics, 2025)
"The Dark Crisis is over, and the Justice League is no more. Now, a new team must rise and protect the Earth...Titans, go! The Teen Titans are ready to grow up. Each member joined as a much younger hero, certain that one day they'd be invited to join the Justice League. But the time has come for them not to join the League...but to replace it! Are the no-longer-teen heroes ready for the big leagues? Danger lurks around every corner as heroes and villains alike challenge the new team before they've even begun."--